Estudo da reação foto-Fenton em diferentes pHs utilizando o complexo ferrioxalato para o tratamento de lixiviado de aterro sanitário - Souza, Adriane Lys de (2015)
Photo-Fenton reactions at a neutral pH of the solution applied to the treatment of sanitary landfill leachate (SLL) was investigated. Using a lab-scale photo-reactor with artificial UV- light source, photo-Fenton reactions and derivations (photolysis, Fenton, photo-Fenton and ferrioxalate), on the decolourisation and aromatic compounds removal were evaluated. Such reactions mediated at a pH of the solution 2.8, present some limitations such as: (i) precipitation and/or volatilization of humic acids in acidification steps, (ii) a partial precipitation of ferric ions complex with the organic pollutants present in SLL; resulting in absorbance removal at 254 nm as well as decolourisation, not represented effective oxidations. However, using ferrioxalate reaction mediated by pH of the solution 6, was possible eliminated the acidification step, keeping the pollutants and iron ion soluble resulting in best oxidations rate. Probably due the stability and solubility associated to ferricarboxylates such as ferrioxalate, as well as the increase of photo-sensibility. After, the main operating parameters of ferrioxalate reaction such as pH of the solution, iron(III):oxalic acid concentrations, H 2 O 2 consumed and amount of energy UV required were investigated. The best results were obtained using: pH of the solution 6.0, 120 mg Fe(III):oxalic acid, consuming approximately 83 mM of H 2 O 2 and ≈ 9 kJ UV L -1 required; leading a ≈ 56% and 45% decolourisation and aromatic compounds removal, respectively. In such conditions, the efficiencies of organic contents reduction as: BOD 5 (≈ 30%), COD (≈ 56%), dissolved organic carbon (DOC) (≈ 33%) and total dissolved nitrogen (TDN) (≈ 26%) were satisfactory and probably improving the treated in terms of SLL-biodegradability (BOD 5 /COD ratio).